GATEWAYS TO POSITIONING INFORMATION AND COMMUNICATION TECHNOLOGY IN ACCOUNTING EDUCATION - Rhodes, Nadia (South African Journal of Higher Education, 2016)
In terms of technology, accounting education has not evolved to the extent required by industry and has created a gap in the knowledge and skills of accounting graduates. This paper reports on how an educational research tool assisted in finding a place for information and communication technology in accounting education. This paper also argues the use of design-based research, within the framework of cultural historical activity theory, to augment the evolution of accounting education within the comprehensive structure of the University of Johannesburg’s diploma programmes. In conclusion, the need to revolutionise the accounting education arena, to align it with accounting practice, has been shown to necessitate the use of the integration model, through which the planned series of interventions are implemented. Keywords accounting education industry information and communication technology (ICT) integration interventions technology.